A novel keratin 13 variant in a four‐generation family with white sponge nevus. Issue 9 (29th July 2017) - de Haseth, Stephanie B.; Bakker, Egbert; Vermeer, Maarten H.; el Idrissi, Hakima; Bosse, Tjalling; Smit, Vincent T.H.B.M.; Terron‐Kwiatkowski, Anna; McLean, W.H. Irwin; Peters, Alexander A.W.; Hes, Frederik J.
Key Clinical Message: We report a novel KRT13 germ line variant that causes white sponge nevus (WSN) with mucosal dysplasia. Genital, vaginal, and cervical WSN were observed in four female patients, of whom two had premalignant cervical lesions at young age. Two of the 12 patients with oral WSN developed oral squamous cell carcinoma. Abstract : We report a novel KRT13 germ line variant that causes white sponge nevus (WSN) with mucosal dysplasia. Genital, vaginal, and cervical WSN were observed in four female patients, of whom two had premalignant cervical lesions at young age. Two of the 12 patients with oral WSN developed oral squamous cell carcinoma.